Assessment of potential climate hazards in Kuala Krai, Kelantan using statistically downscaled regional climate model - Ngu, Jun Jie (2021)

(untitled)
In Peninsular Malaysia, Kelantan is one of the black spot of flood and the rainfall being highly concerned. Therefore, historical rainfall pattern in Kelantan is worth to study and study of the local rainfall pattern in the future is significant to the disaster preparation. In this thesis paper, future precipitation was modelled based on RCP4.5 and RCP8.5 predictors obtained from CanESM2. After obtaining all the data, calibration of the model was carried out by using the SDSM4.2 software that including screening process. In order to determine the reliability of the model, several statistical tests were implemented for model validation. For statistical test of the model, both Pearson correlation analysis and linear regression test indicated that RCP4.5 could simulate the rainfall pattern slightly better than RCP8.5. Although future rainfall prediction is mainly depending on RCP4.5, since both are likely reliable, the rainfall prediction under RCP8.5 was carried out as a potential alternative in the future as well. Based on the outcome, the potential of future flood are only 2 days within next 80 years under RCP4.5 while 7 days within next 80 years under RCP8.5. Therefore, majority of the future precipitation events will not induce severe flood events until the end of 2100